O conceito de ambivalência em D.W.Winnicott - Patricia Ferreira da Costa (2016)
Winnicotts theoretical-clinical approach was to stand as a tireless researcher of Human Nature, taking on the challenge to attend to adult patients and difficult children during almost fifty years of psychoanalytic practice. From such practice, he brought innovations to Psychoanalysis, specially in the field of ambivalence, a significant aspect of his general theory of aggressiveness, which has consequences not only for the individual but also for society. The present work aims at presenting the concept of ambivalence in Winnicotts thought, discussing its characteristics in the stage of concern. In order to do that, a theoretical trajectory will be crafted on the concept of ambivalence in Freud and Melanie Klein, pointing out elements of convergence and divergence in relation to winnicottian theorization. From Winnicotts human maturation theory, some elements of the stages previous to the reach of unitary identity, which can be considered conditional to the constitution of ambivalence, will be thematized. Therefore, this work will present how, in the stage of concern, both the reach of ambivalence, by the integration of the destructive and love impulses, and the capacity for the maintenance of such conquest over ones lifetime, occur. Finally, some contributions from a winnicottian understanding of reach, of loss or of non-reach of capacity for ambivalence will be presented as possibilities for future research in the psychoanalytic field.